Politik Perang Literasi: Sejarah Pendidikan Kristen - Elia Tambunan (Sekolah Tinggi Agama Kristen Terpadu Pesat, 2021)
Innocently, there are scholars of Christian education who see Christian history as clean of political interests an sich. The impact is bad. They have no political analysis competence. In fact, the praxis of education is intertwined with politics. With historical data around the early centuries of Roman Christianity (90-500 A.D), and with historiographical research, it was found that Christian educators also played literacy politics. Paul's writings in New Testament theology, the works of the Bishops, Presbyters, and Deacons, particularly the Roman West and Byzantine East regions under the persecution of several emperors had political tones. The literacy war is the determinant of success in penetrating teachings into the palace circle. Christianity succeeded in overthrowing the ideology of Romanism. Caesar is the guarantee of the freedom of believers in Christ, saving lives from massacre. This paper proposes that learning of political competence and educational literacy are very important at the level of Christian religious higher education and society. Abstrak Dengan polos, ada saja sarjana Pendidikan Kristen yang melihat sejarah agama Kristen bersih dari kepentingan politik secara an sich. Akibatnya buruk. Mereka tidak punya kecakapan analisis politik. Padahal, praksis pendidikan saling menganyam dengan politik. Dengan data sejarah di seputar abad awal kekristenan Romawi (tahun 90-500), dan dengan penelitian historiografi, ditemukan bahwa pendidik Kristen juga memainkan politik literasi. Tulisan Paulus dalam teologi Perjanjian Baru, karya Para Bishop, Presbiter, dan Diaken khususnya wilayah Barat Romawi dan wilayah Timur Bizantium di bawah persekusi beberapa emperor bertonasi politik. Perang literasi menjadi penentu sukses dalam melakukan penetrasi ajaran ke dalam lingkaran istana. Kekristenan sukses menumbangkan ideologi Romanisme. Kaisar adalah jaminan kebebasan orang beriman kepada Kristus, meluputkan nyawa dari pembantaian. Tulisan ini mengusulkan pembelajaran kecakapan politik dan literasi pendidikan sangat penting di aras pendidikan tinggi keagamaan Kristen dan masyarakat.